TANGGAP CABAI MERAH (Capsicum annuum L.) TERHADAP BERBAGAI KONSENTRASI PUPUK ORGANIK CAIR - Faisal Faisal; Abdul Rauf (AGROTEKBIS : JURNAL ILMU PERTANIAN (e-journal), 2021)
The problem faced in the development of chili plants is the high use of inorganic fertilizers at the farmer level. This encourages research using organic fertilizers. This study aimed to study the response of growth and yield of red chili plants to various concentrations of NASA POC. This study used polybags which was carried out in the Duyu village area, West Palu District, Palu City, Central Sulawesi. From November 2019 to March 2020. This study used a randomized block design (RAK) with a one-factor experiment, namely the concentration of P0 = 0 ml.l-1, P1 = 2.5 ml.l-1, P2 = 5.0 ml.l -1, P3 = 7.5 ml.l-1, P4 = 10.0 ml.l-1, and the grouping of seedlings based on the number of leaves was divided into four replications. The results showed that red chili plants had a positive response to NASA's POC. and the pattern is positive linear. The best POC administration was a concentration of 7.5 ml/l on red chili plants, where there was an increase in the number of fruits by 38.5% and fruit weight by 46.2% from plants that were not given POC.